Patient-Ventilator Interaction Testing Using the Electromechanical Lung Simulator xPULM (TM) during V/A-C and PSV Ventilation Mode - Paštěka, Richard; Santos, Pedro; Barros, Nelson; Kolář, Radim; Forjan, Mathias (MDPI, 2021)
During mechanical ventilation, a disparity between flow, pressure and volume demands of the patient and the assistance delivered by the mechanical ventilator often occurs. This paper introduces an alternative approach of simulating and evaluating patient-ventilator interactions with high fidelity using the electromechanical lung simulator xPULM (TM). The xPULM (TM) approximates respiratory activities of a patient during alternating phases of spontaneous breathing and apnea intervals while connected to a mechanical ventilator. Focusing on different triggering events, volume assist-control (V/A-C) and pressure support ventilation (PSV) modes were chosen to test patient-ventilator interactions. In V/A-C mode, a double-triggering was detected every third breathing cycle, leading to an asynchrony index of 16.67%, which is classified as severe. This asynchrony causes a significant increase of peak inspiratory pressure (7.96 +/- 6.38 vs. 11.09 +/- 0.49 cmH(2)O, p < 0.01)) and peak expiratory flow (-25.57 +/- 8.93 vs. 32.90 +/- 0.54 L/min, p < 0.01) when compared to synchronous phases of the breathing simulation. Additionally, events of premature cycling were observed during PSV mode. In this mode, the peak delivered volume during simulated spontaneous breathing phases increased significantly (917.09 +/- 45.74 vs. 468.40 +/- 31.79 mL, p < 0.01) compared to apnea phases. Various dynamic clinical situations can be approximated using this approach and thereby could help to identify undesired patient-ventilation interactions in the future. Rapidly manufactured ventilator systems could also be tested using this approach.

During mechanical ventilation, a disparity between flow, pressure and volume demands of the patient and the assistance delivered by the mechanical ventilator often occurs. This paper introduces an alternative approach of simulating and evaluating patient-ventilator interactions with high fidelity using the electromechanical lung simulator xPULM (TM). The xPULM (TM) approximates respiratory activities of a patient during alternating phases of spontaneous breathing and apnea intervals while connected to a mechanical ventilator. Focusing on different triggering events, volume assist-control (V/A-C) and pressure support ventilation (PSV) modes were chosen to test patient-ventilator interactions. In V/A-C mode, a double-triggering was detected every third breathing cycle, leading to an asynchrony index of 16.67%, which is classified as severe. This asynchrony causes a significant increase of peak inspiratory pressure (7.96 +/- 6.38 vs. 11.09 +/- 0.49 cmH(2)O, p < 0.01)) and peak expiratory flow (-25.57 +/- 8.93 vs. 32.90 +/- 0.54 L/min, p < 0.01) when compared to synchronous phases of the breathing simulation. Additionally, events of premature cycling were observed during PSV mode. In this mode, the peak delivered volume during simulated spontaneous breathing phases increased significantly (917.09 +/- 45.74 vs. 468.40 +/- 31.79 mL, p < 0.01) compared to apnea phases. Various dynamic clinical situations can be approximated using this approach and thereby could help to identify undesired patient-ventilation interactions in the future. Rapidly manufactured ventilator systems could also be tested using this approach.
Patient-Ventilator Interaction Testing Using the Electromechanical Lung Simulator xPULM (TM) during V/A-C and PSV Ventilation Mode
Keywords: biomedical engineering; breathing simulation; electromechanical lung simulator; patient– ventilator interactions; rapidly manufactured ventilator systems testing; biomedical engineering; breathing simulation; electromechanical lung simulator; patient– ventilator interactions; rapidly manufactured ventilator systems testing